Apakah Kimia Sulit? Persepsi Siswa SMA di Indonesia terhadap Kimia - afrahamiryano, afrahamiryano; Horiza, Hevi; Yora, Muharama (Pendidikan Biologi FKIP UMMY, 2025)
This study aims to determine the perception of high school students in Indonesia towards chemistry, as well as to see the relationship between learning difficulties with interest, motivation, and teacher factors. The survey was conducted online with a google form with a cross-sectional survey design and snowball sampling technique. The number of respondents involved in this survey was 412 respondents. The results of the analysis showed that chemistry is included in the difficult category with an average percentage of 65.30%. However, when viewed from the aspect of interest, chemistry is a subject of interest with an average percentage of 71.02%. Furthermore, in terms of motivation, it can be seen that students are quite motivated to learn chemistry with an average percentage of 53.84% and in terms of teachers, it can be seen that teacher factors influence students' perceptions of chemistry with an average percentage of 52.80%. The results of the correlation analysis of the four aspects observed obtained information that there was no relationship between learning difficulties in chemistry with interest, motivation, and teacher factors. However, there is a positive relationship between interest in chemistry with learning motivation, and motivation to learn chemistry with teacher factors. So it can be concluded that although chemistry is considered a difficult subject, it is still in demand by students.